Aflatoxin Contamination in Wheat Flour Samples from Golestan Province, Northeast of Iran - F Ghasemi Kebria; H Joshaghani; AG Chogan; H Keshavarzian; M Namjoo; G Roshandel; S Semnani; N Taheri (Tehran University of Medical Sciences, 2012)
Background: Due to the high toxicity of aflatoxin and its effects on public health, determination of aflatoxin level in Wheat flour samples in the Golestan province, north of Iran was investigated. To examine the effect of seasonal changes, summer and winter sampling was performed with standard sampling methods. Methods: A total of 200 flour samples were collected from 25 factories. HPLC method with immunoaffinity chromatography was used to measure aflatoxin types (G2, G1, B2 and B1). Statistical analysis was performed by the Pearson correlation test, One-way ANOVA and multivariate regression analysis. Results: Mean total aflatoxin levels of samples were 0.82 and 1.99 ng/g in summer and winter, respectively. Aflatoxin B1 levels were detected in 3.1%, 7.4% over permissible limits by worldwide regulations in samples collected in summer and winter, respectively. Aflatoxins in winter were higher than summer. The highest frequency of aflatoxin contamination in winter was B2 (98%) and in summer G1 (51%). The relationship between humidity and rate of aflatoxin B1 and total aflatoxin was significant in winter. Results of multivariate regression were showed the strongest relationship with humidity and aflatoxin level. Despite the contamination of flour samples, there was no contamination higher than the standard limit of Iran Standard Institute. But it was significantly higher than similar studies from other regions. Conclusions: Therefore, with regard to negative impacts of aflatoxin on health, aflatoxin contamination should be considered in future programs. Decrease of aflatoxin contamination may be made practical through reducing wheat storage duration and controlling humidity.